Epidemiology of Visceral Leishmaniasis with Emphasis on the Dynamic Activity of Sand Flies in an Important Endemic Focus of Disease in Northwestern Iran - Ehssan Mozaffari; Hassan Vatandoost; Yavar Rassi; Mehdi Mohebali; Amir Ahmad Akhavan; Eslam Moradi-Asl; Zabihola Zarei; Alieza Zahrai-Ramazani; Esmail Ghorbani (Tehran University of Medical Sciences, 2019)
Background: Leishmaniasis diseases are known to be one of the most important public health problems in World and Iran. Visceral leishmaniasis is considered to be the most serious form and transmitted by sand flies species. The aim of this study was to investigate the dynamic activities of sandflies in northwestern Iran. Methods: This crass-sectional study was conducted from April to December 2018 in Meshkinshahr County, Ardabil Province. Sticky traps have been used to collect sand flies. They are stored in 70% alcohol and finally identified using valid keys. The aspects of the synoptic information were inquired from the Meshkin Shahr weather department and results analyzed for SPSS24. Results: Totally 259 sandflies were collected during study period. From collected samples 78.7% were male and 21.3% female. There were 8 different species. Phlebotomus kandelakii was the most prevalent one (30.8%). The average temperature, relative humidity, and average wind speed was 13.5 °C, 84%, and 2 meters per hour on the onset of sandflies' activity, respectively. These values were 18.3 °C, 85% and 1.5 meters per hour at the peak of their activity and 16 °C, 62% and 5 meters per hour at the final stage of their activity. Sand flies had one peak in July which is strongly influenced by temperature and humidity conditions. Two species of Ph. kandelakii and Phlebotomus perfilewi transcaucasicus, had the highest activity in this endemic area. Conclusion: The results of current study will provide a guideline for control of diseases in the country.